2005
DOI: 10.1111/j.1526-4610.2005.00240.x
|View full text |Cite
|
Sign up to set email alerts
|

Patterns and Predictors of Prescription Medication Use in the Management of Headache: Findings From the 2000 Medical Expenditure Panel Survey

Abstract: The observed variation in prescription medication use by drug class and sociodemographic characteristics suggests strategies are needed for improving current prescribing patterns in this patient population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 37 publications
0
22
0
Order By: Relevance
“…In reality, clinicians presently employ a gamut of medications for migraine therapy, some with firm evidence of efficacy, others lacking substantiation of positive effects [5,23].To promote improved use of drugs, the Consortium's guidelines rank acute medications. The highest ranking signifies that multiple randomized clinical trials, directly relevant to the recommendations, yield a consistent pattern of a statistically significant clinical benefit [22].…”
Section: Migraine Treatmentmentioning
confidence: 98%
See 1 more Smart Citation
“…In reality, clinicians presently employ a gamut of medications for migraine therapy, some with firm evidence of efficacy, others lacking substantiation of positive effects [5,23].To promote improved use of drugs, the Consortium's guidelines rank acute medications. The highest ranking signifies that multiple randomized clinical trials, directly relevant to the recommendations, yield a consistent pattern of a statistically significant clinical benefit [22].…”
Section: Migraine Treatmentmentioning
confidence: 98%
“…Of note, studies examining prescribing patterns cite aspirin or acetaminophen combined with butalbital and caffeine as one of the most common, acute migraine drugs selected by US physicians [5,23,44]. Yet, not a single placebo-controlled, randomized trial has concluded that butalbital-combination products are more effective than placebo for migraine [22].…”
Section: Migraine Treatmentmentioning
confidence: 99%
“…30 Furthermore, the use of butalbital-containing products and narcotics doubles the risk for episodic migraine to evolve into chronic daily headache. 31 In clinical practice, problems associated with use of butalbital-containing products are so rampant that some headache-specialist physicians have proposed banning butalbital-containing products. 32 Almost half of the survey's key informants recommend butalbital-containing products as a possible migraine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…6 Despite advances in treatment, however, most patients with chronic headache continue to be undertreated or misdiagnosed. [7][8][9] Given that patients with chronic headache disorders utilize more health care resources and use more medication compared to patients with other diseases, 5,10 multiple authors have advocated the use of interdisciplinary care when managing these patients. 6,[11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] Several studies on the effect of interdisciplinary care in patients with headache have shown reduced frequency of headaches; reduced usage of attackaborting medication; reduced levels of depression, anxiety, and overall disability; and decreased absence rate from work.…”
Section: Introductionmentioning
confidence: 99%